2018
DOI: 10.1089/acm.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Current Evidence on Heart Rate Variability Biofeedback as a Complementary Anticraving Intervention

Abstract: Despite the limitations of this review, there is beginning evidence that HRVB and CB training can be of significant therapeutic potential. Larger clinical trials are needed with methodological improvements such as longer treatment duration, adequate control conditions, measures of adherence and compliance, longitudinal examination of craving changes, and more comprehensive methods of craving measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 79 publications
(129 reference statements)
1
21
0
Order By: Relevance
“…It was posited that HRV biofeedback could enhance communication between neural and cardiovascular systems that modulate physiological arousal in response to internal and external cues that are antecedent to substance use, thus increasing behavioral flexibility and reducing relapse risk [4••, 42]. A recent systematic review [43] suggests that HRV biofeedback may reduce craving, citing work involving short [3 sessions; 44], moderate [6 sessions ; 45, 46], and longer term [8 sessions ; 47, 48] interventions. Studies by Penzlin and colleagues also showed HRV biofeedback led to reductions in anxiety in patients with alcohol use disorder [46], and a trend towards lower alcohol use relapse at 1-year follow-up compared to controls [45].…”
Section: Changing Cardiovascular Physiology Leads To Clinical Benefitmentioning
confidence: 99%
“…It was posited that HRV biofeedback could enhance communication between neural and cardiovascular systems that modulate physiological arousal in response to internal and external cues that are antecedent to substance use, thus increasing behavioral flexibility and reducing relapse risk [4••, 42]. A recent systematic review [43] suggests that HRV biofeedback may reduce craving, citing work involving short [3 sessions; 44], moderate [6 sessions ; 45, 46], and longer term [8 sessions ; 47, 48] interventions. Studies by Penzlin and colleagues also showed HRV biofeedback led to reductions in anxiety in patients with alcohol use disorder [46], and a trend towards lower alcohol use relapse at 1-year follow-up compared to controls [45].…”
Section: Changing Cardiovascular Physiology Leads To Clinical Benefitmentioning
confidence: 99%
“…Specifically, SPB interventions coupled with the use of biofeedback (i.e., where participants are able to directly see the effects of SPB on their heart rate patterns via a dedicated device) were shown to be effective in reducing alcohol dependence (Penzlin et al, 2017;Penzlin et al, 2015) and overall cravings (Alayan et al, 2019;Eddie et al, 2018). The long-term physiological effects of SPB on CVA make it a promising alternative non-medical treatment for addictions (Alayan, Eller, Bates, & Carmody, 2018;Bates, Lesnewich, Uhouse, Gohel, & Buckman, 2019;Eddie, Vaschillo, Vaschillo, & Lehrer, 2015;Leyro, Buckman, & Bates, 2019). Although, lLong-term SPB interventions have been shown to increase CVA, nevertheless, much less is known about the effects of short-term interventions.…”
Section: Influence Of a Single Slow-paced Breathing Session On Cardiac Vagal Activity 1 Introductionmentioning
confidence: 99%
“…As shown by several meta-analyses and systematic reviews, SPB coupled to HRV biofeedback interventions typically involving a series of sessions with a practitioner spread over a couple of weeks, and often completed with home practice, lead to improvements regarding stress and anxiety symptoms (Goessl et al, 2017), depressive symptoms (Pizzoli et al, 2021), fibromyalgia (Reneau, 2020), controlling substance craving (Alayan et al, 2018), enhancing executive functions (Tinello et al, 2021), and improving sports performance (Pagaduan, Chen, Fell, & Xuan Wu, 2020;Pagaduan, Chen, Fell, & Xuan Wu, 2021). However, despite the growing use of HRV biofeedback interventions, questions remain regarding the underlying mechanisms of this technique.…”
Section: Introductionmentioning
confidence: 99%